Study of the environmental and individual factors of autoimmune diseases in the microregion of Águas Formosas – Minas Gerais State, Brazil - Tolentino Junior, Dilceu Silveira (2021)
Autoimmune diseases lead to numerous limiting conditions. Their incidence and prevalence are known to be affected by several factors; and there is an absence of data in areas of economic vulnerability. The aim of this study was to access the epidemiological profile of autoimmune diseases in the public health system of the microregion of health of Águas Formosas, and to evaluate possible factors involved in the development of these diseases. This was an epidemiological study with a cross-sectional, survey-type, descriptive and exploratory. All patients were selected according to the inclusion criteria, and individual interview was conducted during home visits to apply a sociodemographic questionnaire with 20 variables associated with autoimmune diseases. In this study, it was observed that the municipalities of Machacalis, Umburatiba and Crisólita exhibited prevalence of autoimmune diseases above 90 cases per 10,000 of the population, and the other municipalities showed prevalence between 50 and 60 cases. In the microregion, a total of 407 cases of autoimmune diseases were observed, distributed in 24 different diseases, with a general prevalence of 673.69/100,000 of the population. Hashimoto's Thyroiditis, Graves' Disease, Vitiligo, Rheumatoid Arthritis, Psoriasis, Type 1 Diabetes Mellitus and Systemic Lupus Erythematosus, represent 47% of the cases. This was the first study that addresses the prevalence of autoimmune diseases in the microregion. The lack of registration or diagnosis is a factor that needs to be overcome in new studies to improve the knowledge of autoimmune diseases in this region.